Pengaruh Kemasan Produk dan Variasi Menu terhadap Daya Tarik Konsumen pada UMKM Jasa Catering - Sri Utami (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to evaluate and explore the contribution of Micro, Small, and Medium Enterprises (MSMEs) to Indonesia’s economic dynamics, focusing on their capacity to absorb labor, their role in contributing to the Gross Domestic Product (GDP), as well as the various challenges and development strategies they face. MSMEs have proven to be a key pillar of the national economy, particularly due to their resilience during crises and their ability to support equitable development. This study employs a descriptive qualitative approach through literature review and direct observation of MSME activities. The findings indicate that MSMEs contribute more than 60% to the national GDP and absorb up to 97% of the workforce, reaffirming their significant role in job creation and poverty reduction. However, MSMEs continue to face multiple obstacles, such as limited access to capital, low utilization of technology, and difficulties in reaching wider markets. Therefore, policy synergy among the government, industry players, and financial institutions is needed to enhance MSME competitiveness amid the challenges of digitalization and globalization. The study concludes that strengthening support systems for MSMEs is essential to promoting sustainable and inclusive economic growth.